APLIKASI REAKTOR SISTEM SINAMBUNG DAN TEKNOLOGI MEMBRAN PADA PRODUKSI ENZIM A-AMILASE OLEH Bacillus subtilis - Mahyudin AR; Sumaryanto Sumaryanto (JURNAL ILMU KEFARMASIAN INDONESIA, 2003)
a-Amylase enzyme (endoamylase) is produced for hydrolysis of 1,4-glikosidic binding from starch to maltose in food and non food industries. Due to increasing production capacity, continuous of fermentation process and maintaining the enzyme activity can be achieved with CSTR (Continuous Stirred Tank Reactor), an alternative for batch process replacement. 3,51 Reactor combined with microfiltration membrane under specific conditions such as : pH, molasses-urea medium, temperature, and agitation are adjusted to 8,37° C, and 250 rpm. The result obtained showed that in 1 vv m aeration Bacillus subtilis ATCC 6633 reached an enzyme specific activity of 93 Unit/mg protein during 20 hours fermentation. By continuous fermentation using a medium containing 3 % molasses - 0,6 % urea, these bacteria excrete an enzyme with a specific activity of 60 U/mg protein during 22 hours fermentation. It was shown that a production during 96 hours gave an enzyme production with a specific activity of 90 U/mg protein.